The effects of submaximal exercise on a treadmill on the recovery of the stiffness index and reflection index in men with untreated hypertension - Miętkiewska-Szwacka, Kamila; Magdalena Kujawska-Łuczak; Tomasz Piorunek; Szczepan Cofta; Karolina Hoffmann; Katarzyna Grabańska-Martyńska; Magdalena Roszak; Ewa Wysocka; Maciej Cymerys (Journal of Medical Science, 2021)
Aim. Increased arterial stiffness is a risk factor for cardiovascular disease (CVD). Adult men with untreated hypertension are at risk of future CVD. The study aimed to compare the effects of a submaximal exercise on the recovery of the two descriptors of arterial pressure waveform, i.e. stiffness index (SI) and reflection index (RI), between men with untreated hypertension (HA) and healthy peers.Material and Methods. The study included 70 Caucasian men with untreated primary HA and 30 normotensive men. Blood pressure, SI and RI were determined by photoplethysmography before and 6 minutes after a submaximal (up to 85% of age-predicted maximal heart rate) exercise on a treadmill.Results. Baseline SI was higher in HA than control men (6.06 [0.66] vs. 6.61 [0.84] m/s; p=0.0019) and remained significantly increased during post-exercise recovery only in HA men (7.59 [1.6] vs. 6.18 [0.85] m/s; p
Keywords: arterial stiffness; exercise; post-exercise recovery; hypertension